BENTUK DAN MAKNA VERBAL SERTA FUNGSI PERISTILAHAN PADA IKLAN MOBIL DAN SEPEDA MOTOR DI SURAT KABAR SOLOPOS - Putri Sri Winarsih; Markhamah Markhamah; Andi Haris Prabawa (Jurnal Penelitian Humaniora, 2015)
The purpose of this study to describe: (1) the verbal form of terminology used in car and motorcycle advertisement found in the Solopos, (2) the meaning of terminology used in car and motorcycle advertisement found in the Solopos, and (3) the function of terminology used in car and motorcycle advertisement found in the Solopos. This study was a qualitative research and the object of the study is verbal form, meaning, and function used in car and motorcycle advertisement found in the Solopos. Data collection technique used is documentation and data analysis used is referential technique. The results of the study are as follows: (1) the verbal form of terminology used in car and motorcycle advertisement are of three kinds, namely: (a) the term that indicates excellence, (b) the term that indicates appearance, and (c) the term that denotes a pleasant thing. (2) the message of terminology used in car and motorcycle advertisement includes: (a) in terms of its nature there are two types of meaning: denotative and connotative meaning, (b) in terms of its relation to the reference there are synonymy, polysemy, homonymy, hiponimi and antonym. (3) the function of terminology used in car and motorcycle advertisement are as follows: (a) to introduce a product identity that is informed and explain the differences in products with other products, (b) to communicate the product concept, the benefits and advantages functional, psychological, and target markets, (c) to lead to the use of old and new products to the market, (d) to inform the sales and purchases to stimulate a wider distribution, (e) to establish and maintain product image product positioning in the target markets, and (f) to confront the problem related to competition among products.